Pregnane X receptor-mediated liver growth: a controlled clinical trial in healthy volunteers and identification of the role of AKT–MTOR pathway in mouse - Piia Lassila; Mikko Karpale; Outi Kummu; Aaron Stahl; Aki Käräjämäki; Eija Pääkkö; Helen Sophie Hammer; Albert Braeuning; Oliver Pötz; Markus Templin; Janne Hukkanen; Jukka Hakkola (Archives of Toxicology, 2026)
Abstract Pregnane X receptor (PXR) is a nuclear receptor acting as a master xenobiotic receptor for many exogenous chemicals. Activation of PXR has been linked to liver growth in mice, usually via interaction with Yes-associated protein (YAP), but this adaptive response has not been observed in humans. We investigated the effect of human PXR agonist, rifampicin, on liver size in a controlled clinical trial in healthy volunteers. Moreover, we developed a novel protocol to reveal mechanisms of PXR-mediated liver growth in mice. One-week rifampicin treatment caused a 2.7% mean increase in liver volume-to-body weight ratio without affecting liver fat content in human volunteers (n=16). Pxr −/− mice were transduced with adenovirus carrying either murine PXR or green fluorescent protein and both groups were treated with pregnenolone−16α-carbonitrile (PCN) for 0 to 4 days. In this setup, activation of PXR with PCN significantly increased liver size in male mice already after 1-day PCN treatment and the liver growth was further enhanced after 4 days. No significant liver enlargement was observed in female mice. 4-day PCN treatment also improved glucose tolerance in the male mice. RNA-sequencing revealed upregulation of genes and pathways involved in proliferation. DigiWest protein profiling and immunoblotting revealed increased activity of AKT–mammalian target of rapamycin (MTOR) pathway in the male mice. In contrast, we did not observe YAP activation. Our results indicate that PXR activation induces liver growth and activates proliferative AKT–MTOR pathway in male mice and may also induce liver growth in humans.